PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI SEKSUAL DALAM PERNIKAHAN DINI (STUDI PUTUSAN MAHKAMAH AGUNG INDONESIA NOMOR 690K/PID.SUS/2010) - Dewi Ervina Suryani; Madiasa Ablisar; Marlina Marlina; Jelly Leviza (Universitas Sumatera Utara, 2015)
ABSTRACT Sexual exploitation of children is a serious violation of Human Rights. Handling of this problem is being the main destination countries in the world including Indonesia. Child marriage is one of sexual exploitation crimes againts children, specially to the girls. It has increased year by year. Decision of court with Number 690K/PID.SUS/2010 is one of sexual exploitation of children in the marriage. Based on the survey results revealed that the settings on the prohibition of sexual exploitation in the early marriage is not expressly regulated in the law, but the actions are prohibited. Judge's decision not to accommodate the implementation of the protection of children who are victims of sexual exploitation in the early marriage, because it is concentrated to criminal punishment only. Recommended to the government to immediately assess, formulate, and implement policies abolition of child marriages below the age of criminal sanctions is high, in order to create legal certainty. Revise the Marriage Act by raising the marriage age limit for women. Conduct an education and specialized training to judges on the application of the law of the child, as well as involving them in seminars or forums that discuss the issue of children, in order to create a child protection efforts.